6102 Sayılı Türk Ticaret Kanunu’nun anonim şirket genel kuruluna özgü düzenlemeleri - (:unkn) unknown (My University, 2008)
Genel kurul, anonim şirketin kanunen zorunlu organıdır ve tüm pay sahipleri genel kurulu oluşturur. Bu çalışmada, 6102 sayılı Türk Ticaret Kanunu’nun genel kurul organına bakışı ve bu organa ilişkin düzenlemeleri ele alınmıştır. Yeni Türk Ticaret Kanunu genel kurulun organ niteliğini koruyarak halihazırdaki mevcut yapısını değiştirmemekle birlikte genel kurulun işleyişini iyileştiren, güncel ihtiyaçlara cevap veren ve hukuki boşlukları dolduran yeni hükümler içermektedir. İşte, anılan Kanundaki bu hükümler bu çalışmanın konusudur.

General shareholders’ meeting is a legally mandatory body of joint-stock com- pany and it consists of all shareholders. In this study, the Turkish Commercial Code’s (6102) perspective and regulations on the body of the general shareholders’ meeting has been evaluated. The new Turkish Commercial Code, does not change over the body characteristics of the general shareholders’ meeting. It improves the functioning of the general shareholders’ meeting where it satisfies the current needs and fills the legal gaps. Therefore, assessment of the above mentioned Code and its articles about general shareholders’ meeting are the main topic of this study.
Regulations in the Turkish Commercial Code (6102) on the joint- stock company’s general shareholders’ meeting
Keywords: Hukuk